Passionate patriotism or European enslavement - Manić, Mihajlo P. (Collection of Papers of the Faculty of Philosophy in Priština, 2015)
The study "A passionate patriotism or European enslavement", from the eminent professor Petar Anđelković, represents another attempt by this author to analyze the Serbian society in the context of its development. This book is a logical continuation of his essay published in 2013, Serbian Society—without past, what is our present?, and represents a symbiosis of texts that the author has already published and in which he addresses the very relevant questions of Serbia's relations with the new world order and with the inevitable role of the European Union, as an existential challenge to the very existence of the Serbian society.
Keywords: internation relations; society; European Union; globalization; Serbia